Does a Passport Get You a Degree? Citizenship Reform and Educational Achievement - Celina Proffen; Franziska Riepl (CESifo GmbH, 2024)
This paper examines the impact of introducing birthright citizenship in Germany on the educational trajectories of second-generation immigrants. Our identification strategy exploits a legal change in 2000 that granted children of foreigners with longtime residency automatic citizenship at birth. Using high-quality census data, we show that the reform contributes to closing pre-existing educational gaps in secondary school track choice and completion. These findings also hold when relying exclusively on within-household variation across siblings. We provide evidence for the underlying mechanisms, highlighting the roles of higher expected returns to education and of an increased sense of belonging to Germany.
Keywords: J15; J24; K37; O15; 330; birthright citizenship; education; human capital; integration; immigration